PEMEKARAN PERAN MANUSIA DALAM PENINGKATAN TOTAL QUALITY MANAGEMENT (TQM) DI BIDANG PENDIDIKAN - Tambunan, Frietz R. (UNIKA Santo Thomas, 2004)
The implementation of regional autonomy after the end of the New Order Regime in Indonesia has become the focus of many discussions nowadays. This new spirit has affected many sectors in the society, including education. One of the elements of the regional autonomy is the demand for decentralisation in education. That means the distribution of the power from the center to the pheriphery. Needless to say, decentralisation is the substance of every educational reform but this demand has become greater due to the new demand of the implementation of the Total Quality Management in education field. Within this perspective, this paper will discuss the implementation of the TQM in education which in its very substance means the distribution of some power from the higher authority to the lower one and in the second place the empowering of the development of the human resources in the shoop-floor level. As happens in the industrial sector, the quality of product much depends on the quality of the workers who involve in the process of production. The quality of the education result – the educated and skilled person – depends on the quality of those who are involved in the educational process.